Agronomic performance and protein content of Pereskia aculeata Mill. Using organic chicken manure fertilizer - Guimarães, José Rodrigo de Araújo [UNESP]; Gomes, Jordany Aparecida de Oliveira [UNESP]; Teixeira, Daniela Aparecida [UNESP]; Bonfim, Filipe Pereira Giardini [UNESP]; Evangelista, Regina Marta [UNESP] (Southern Cross Publishing, 2019)
Pereskia aculeata Mill is a rustic and perennial plant, developing well in various types of soil, both in the shade and in the sun. It is a plant with high nutritional potential indicated as an alternative food. The current study aimed to evaluate yield and protein content of Pereskia aculeata Mill. under different levels of organic chicken manure fertilizer. A completely randomized design was conducted with five treatments and four replicates. Replications consisted of two experimental plots that contained 'ora-pro-nobis' plant. The treatments referred to different levels of organic chicken manure fertilizer, such as T1_control (soil + 0 kg m -2 of chicken manure); T2_(soil + 2 kg m -2 of chicken manure); T3_(soil + 4 kg m -2 of chicken manure); T4_(soil + 6 kg m -2 of chicken manure); T5_(soil + 8 kg m -2 of chicken manure). The following traits were evaluated: shoot length (cm); total leaf area; leaf number; root length (cm); root volume (mL); root dry mass (g); shoot fresh mass (g); shoot dry mass (g) and crude protein content (g 100g -1 ). Results indicated significant increase in yield and protein content of Pereskia aculeata (12.21 g 100g -1 ) by enhancing the levels of chicken manure. Therefore, a recommendation of 3.5 kg m -2 of chicken manure can be made on soils of average fertility using in organic farming systems under similar conditions to this experiment.
Keywords: Alternative food; Cactaceae; Edible plants; Non-conventional plant; Pereskia aculeata Mill.